Early flowers and angiosperm evolution - Friis, Else Marie; Crane, Peter R.; Pedersen, Kaj Raunsgaard (Cambridge, U. K. : Cambridge University Press, 2011)
'The recent discovery of diverse fossil flowers and floral organs in Cretaceous strata has revealed astonishing details about the structural and systematic diversity of early angiosperms. Exploring the rich fossil record that has accumulated over the last three decades, this is a unique study of the evolutionary history of flowering plants from their earliest phases in obscurity to their dominance in modern vegetation. The discussion provides comprehensive biological and geological background information, before moving on to summarise the fossil record in detail. Including previously unpublished results based on research into Early and Late Cretaceous fossil floras from Europe and North America, the authors draw on direct palaeontological evidence of the pattern of angiosperm evolution through time. Synthesising palaeobotanical data with information from living plants, this unique book explores the latest research in the field, highlighting connections with phylogenetic systematics, structure and the biology of extant angiosperms'--
Includes bibliographical references (p. 501-572) and index.
Keywords: Angiosperms, Fossil; Angiosperms -- Evolution